DDRE-29. DE NOVO PYRIMIDINE SYNTHESIS IS A TARGETABLE VULNERABILITY IN IDH-MUTANT GLIOMA. (25th March 2021) - Shi, Diana D; Wang, Adam C; Levitt, Michael M; Endress, Jennifer E; Xu, Min; Gao, Wenhua; Khanal, Januka; Bonal, Dennis; Kornblum, Harley I; Nguyen, Quang-De; Gradl, Stefan; Sutter, Andreas; et al.
Abstract: 70–90% of lower-grade gliomas and secondary glioblastomas harbor gain-of-function mutations in isocitrate dehydrogenase 1 ( IDH1 ), causing overproduction of the oncometabolite ( R )-2-hydroxyglutarate [( R )-2HG]. Although inhibitors of mutant IDH enzymes are effective in other cancers, including leukemia, they have shown guarded efficacy in preclinical and clinical brain tumor studies, thus underscoring the need to identify additional therapeutic targets in IDH mutant glioma. We sought to identify tumor-specific metabolic vulnerabilities induced by IDH1 mutations that could be exploited therapeutically. To uncover such vulnerabilities, we conducted a chemical synthetic lethality screen using isogenic IDH1 mutant and IDH1 wild-type (WT) glioma cell lines and a novel metabolic inhibitor screening platform. We discovered that IDH1 mutant cells are hypersensitive to drugs targeting enzymes in the de novo pyrimidine nucleotide synthesis pathway, including dihydroorotate dehydrogenase (DHODH). This vulnerability is specific because inhibitors of purine nucleotide metabolism did not score in our screen. We validated that the cytotoxicity of pyrimidine synthesis inhibitors is on-target and showed that IDH1 mutant patient-derived glioma stem-like cell lines are also hyperdependent on de novo pyrimidine nucleotide synthesis compared to IDH1 WT lines. To test pyrimidine synthesis dependence of IDH1 mutant gliomas in vivo, we used a brain-penetrent DHODH inhibitor currently undergoing evaluation in leukemia patients, BAY 2402234. We found that BAY 2402234 displays monotherapy activity against gliomas in an orthotopic xenograft model of IDH1 mutant glioma, with an effect size that compared favorably with radiotherapy. We also developed novel genetically engineered and allograft mouse models of mutant IDH1-driven anaplastic astrocytoma and showed that BAY 2402234 blocked growth of orthotopic astrocytoma allografts. Our findings bolster rationale to target DHODH in glioma, highlight BAY 2402234 as a clinical-stage drug that can be used to inhibit DHODH in brain tumors, and establish IDH1 mutations as predictive biomarkers of DHODH inhibitor efficacy.